Strategic Government for Handling Pandemic Covid-19 in Indonesia - Rd Nurizki Abriyanti (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Indonesia is one of the countries affected by Covid-19 and even accounts for 7.8 percent of the death rate and is one of the highest in the world. During the increasing number of cases, Indonesia accepted foreign workers from China. This policy shows that the Indonesian government cannot ignore the economic aspects of the Covid-19 pandemic. The author considers it important to study the Indonesian government's strategy in the Covid-19 outbreak from an economic perspective. The method used in this article is a descriptive qualitative approach. This means that the author conducts a simple study by describing the state of an object to be studied at this time, based on the facts found (fact-finding), to then be placed with the relevant theory. The conclusion from this research is that the government needs policies to save people's lives during the Covid-19 pandemic, including social rights; physical tickets; use of personal protective equipment; personal hygiene; work and study at home and, delay all activities.